After the negotiations: assessing the impact of free trade agreements in Southern Africa - Lewis, Jeffrey D.; Robinson, Sherman; Thierfelder, Karen (International Food Policy Research Institute, 1999)
After protracted and difficult negotiations, agreement was recently reached on the dimensions of a South African-EU free trade deal. Because of South Africa's prominence in the sub-region, implementation of this agreement will have an impact not only on South Africa, but on all the SADC economies. This paper traces how this impact may be felt over time, using a multi-region model constructed to focus on the determination of sectoral and geographic trade patterns. By separatelymodeling South Africa and the rest of southern Africa, the model can be used to evaluate how alternative SADC regional trade strategies can influence how the EU deal affects the region's economies; by distinguishing among major trading partners (EU, North America, East Asia), the simulations can help illuminate how the trade deal will likely affect current trade patterns The empirical results lead to a number of conclusions: (1) trade creation dominates trade diversion for the region under all FTA arrangements; (2) the rest of southern Africa benefits from an FTA between the EU and South Africa — the recently signed bilateral agreement is not a “beggar thy neighbor” policy; (3) the rest of southern Africa gains more from zero-tariff access to EU markets than from a partial (50 percent) reduction in global tariffs; and (4) the South African economy is not large enough to serve as a growth pole for the region. Access to EU markets provides substantially bigger gains for the rest of southern Africa than does access to South Africa.